Detection of Aflatoxigenic Aspergillus Flavus in Maize Grains and Soils in Sulaimani Province using Molecular Approaches. - Shekhany, Khattab A. M.; Rostam, Shkar R.K. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Aflatoxins are potent carcinogens produced by A. flavus as secondary metabolites. They have the ability to contaminate a large number of food, which ultimately affect the human population. Investigating the incidences of aflatoxigenic species of A. flavus in the local area samples were the aim of current study. Samples were collected randomly from soil and maize grains in the Sulaimani governorate. Morphological features and specific PCR-based protocol were used for identification of A. flavus isolates. This PCR protocol was based on the multi-copy internal transcribed region of the rDNA unit (ITS1-5.8S-ITS2 rDNA), which allowed discrimination from other closely related species. Molecular approach has been used for detection of aflatoxigenicity of the A. flavus isolates. In this study out of eighteen isolates only seven isolates were molecularly and morphologically identified as A. flavus. The aflatoxigenicity of these seven isolates were detected by molecularly method which successfully amplify two structural genes (aflD and aflO) out of three structural genes, and one regulatory gene (aflR). Furthermore, no specific amplicon for (aflP) was obtained in this study.
Keywords: Aspergillus flavus aflatoxinpolymerase chain reaction PCR detection